2000
DOI: 10.1137/s0895479898340299
|View full text |Cite
|
Sign up to set email alerts
|

On Lagrangian Relaxation of Quadratic Matrix Constraints

Abstract: Abstract. Quadratically constrained quadratic programs (QQPs) play an important modeling role for many diverse problems. These problems are in general NP hard and numerically intractable. Lagrangian relaxations often provide good approximate solutions to these hard problems. Such relaxations are equivalent to semidefinite programming relaxations.For several special cases of QQP, e.g., convex programs and trust region subproblems, the Lagrangian relaxation provides the exact optimal value, i.e., there is a zero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
107
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(111 citation statements)
references
References 48 publications
1
107
0
Order By: Relevance
“…We briefly describe this connection and then we consider more general models based on semidefinite optimization. The key tool here is the following theorem of Anstreicher and Wolkowicz [15], which can be viewed as an extension of the Hoffman-Wielandt theorem.…”
Section: Relaxations Using Semidefinite Optimizationmentioning
confidence: 99%
See 2 more Smart Citations
“…We briefly describe this connection and then we consider more general models based on semidefinite optimization. The key tool here is the following theorem of Anstreicher and Wolkowicz [15], which can be viewed as an extension of the Hoffman-Wielandt theorem.…”
Section: Relaxations Using Semidefinite Optimizationmentioning
confidence: 99%
“…A quadratic programming (QP) relaxation for the min-cut problem is derived in [14]. That convex QP relaxation is based on the QP relaxation for the QAP, see [15,25,26]. Numerical results in [14] show that QP bounds are weaker, but cheaper to compute than the strongest SDP bounds, see also Sect.…”
Section: Linear and Quadratic Programming Relaxationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Let (Y, y) be feasible for GPP ZWN and of block form (2). We construct from Y a feasible point Y ∈ S n for GPP RS in the following way:…”
Section: It Is Clear That Formentioning
confidence: 99%
“…Alizadeh [1] proved that the Donath-Hoffman bound is the dual of a semidefinite program (SDP). Also, Anstreicher and Wolkowicz [2] showed that the Donath-Hoffman bound can be obtained using the Lagrangian dual of an appropriate quadratically constrained problem.…”
Section: Introductionmentioning
confidence: 99%